TRANSFORMASI KOMUNIKASI NON VERBAL PAYAS AGUNG BADUNG PADA UPACARA PERKAWINAN BAGI UMAT HINDU DI KOTA DENPASAR - Tjokorda Istri Bintang Kencana Dewi; I Wayan Wastawa; I Dewa Ketut Wisnawa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
The transformation in Balinese bridal make-up and dress, especially regarding the details on the face and head decoration of the bride, is not solely due to the wishes of the bride herself, but because of the demands of the times. The transformation of traditional Balinese bridal make-up and clothing into the form of modified bridal make-up and clothing cannot be separated from the development of the socio-cultural dynamics of the Denpasar community itself. The dynamic itself can be understood as starting from the emergence of a new trend in Balinese life cycle rituals, especially in wedding ceremonies, namely the emergence of pre-wedding culture among young people which began in the 2001s.The implications of the transformation in Balinese bridal make-up and clothing have had various implications for the social life of people all over the world. The changes that occur in society are caused by three main factors, namely; the need for democratization, advances in science and technology and globalization.Implications for social dynamics The development of this kind of globalization will certainly bring about social change. One of the most prominent socio-cultural changes that occurred as a result of the development of this globalization era was the strengthening of the consumptive behavior of the community, including the people of Denpasar.The transformation of values in the field of Balinese make-up and bridal clothing, either at the level of nista, middle or at the level of Payas agung is due to the development of an increasingly modern society. This can not be separated from the existence of a new order in the development of the social system in this country, including the social order of the Denpasar community, which has implications for various aspects of community life, such as in the field of education